Pengaruh Kepemimpinan, Masa Kerja dan Motivasi terhadap Kinerja Karyawan Back Office - Puspitasari, Ikke; Kemal Taufik; Nurmansyah, Nurmansyah (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
The purpose of this research is to determine and analyze the influence of leadership, length of service, and motivation simultaneously on the performance of back-office employees at PT. Indomarco Prismatama Semarang Branch. This research uses a concurrent mixed methods strategy, which combines quantitative data with qualitative data. Research results: From the results of statistical data analysis, it can be seen that leadership, length of service, and motivation partially and simultaneously influence the performance of PT back office employees. Indomarco Prismatama Semarang Branch. This can be interpreted to mean that these three factors are factors that influence the high and low performance of back-office employees in the company. In conclusion, there is a significant and positive influence of leadership, length of service and motivation simultaneously on the performance of PT back office employees. Indomarco Prismatama Semarang Branch. This shows that increasing these three variables simultaneously will also increase performance.  Keywords: Employee Performance, Leadership, Years of Service